Flipbook-Based E-Module Media to Improve Learning Outcomes of Central Javanese Traditional Dance Material - Rasyid, Brilyan Ardliansyah Al; Nurharini, Atip (LPPM Undiksha, 2025)
In this increasingly developing era, teachers are expected to be creative in creating learning media. In dance subjects where students sometimes have difficulty understanding the material, more interesting learning media are needed. This study aims to develop flipbook-based e-module learning media to improve student learning outcomes. This type of research is development. The model used is ADDIE. The methods used in data collection are observation, interviews, tests, questionnaires. Data collection instruments use questionnaires and test questions. The subjects used in this study were teachers, students, learning media experts, and learning material experts. Data analysis techniques used quantitative, qualitative, and N-gain descriptive. The results of the study showed the level of feasibility of the media expert test media 73.33% and the material expert test 85%, and the pretest and posttest learning outcomes of students in small-scale trials had an N-Gain value of 0.69. In large-scale trials, an N-Gain value of 0.71 was obtained. It was concluded that flipbook-based e-module media is feasible for use in the learning process of Central Javanese traditional dance material and can improve student learning outcomes.